2019
DOI: 10.22616/rrd.25.2019.050
|View full text |Cite
|
Sign up to set email alerts
|

Botrytis genus fungi as causal agents of legume diseases: A review

Abstract: Grain legumes are important crops for the diversification of European farming system. In Latvia, the areas of faba beans (Vicia faba) and field peas (Pisum sativum) are increasing and legumes that have not been previously cultivated are sown. Globally, the important causal agent of legume diseases belongs to the genus Botrytis. Botrytis spp. cause significant losses in faba beans and infect a wide range of legume crops. Currently, the composition, pathogenicity and biological characteristics of Botrytis specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…To our knowledge, this is the first report of the presence of B. caroliniana in Europe. Other species, such as B. fabiopsis or the new species B. euroamericana, have been observed in Europe; however, information on their geographical presence is scarce [36,37]. B. caroliniana EXF-17025 (No.…”
Section: Identification Of the Isolated Fungal Strains From Vineyards...mentioning
confidence: 99%
“…To our knowledge, this is the first report of the presence of B. caroliniana in Europe. Other species, such as B. fabiopsis or the new species B. euroamericana, have been observed in Europe; however, information on their geographical presence is scarce [36,37]. B. caroliniana EXF-17025 (No.…”
Section: Identification Of the Isolated Fungal Strains From Vineyards...mentioning
confidence: 99%
“…These findings were supported by subsequent research (Fan et al, 2015;Elad et al, 2016). B. fabiopsis has been found in Latvia on faba bean (Brauna-Morževska et al, 2019). DNA analysis showed that B. cinerea comprised two distinct populations leading to the separation of B. pseudocinerea, which is similar in morphology but genetically distinct from B. cinerea (Plesken et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…DNA analysis showed that B. cinerea comprised two distinct populations leading to the separation of B. pseudocinerea, which is similar in morphology but genetically distinct from B. cinerea (Plesken et al, 2015). Thus, at least four species of Botrytis have been associated with the chocolate spot disease of faba bean leading to hypothesize that the causal agents of a chocolate spot on faba bean in northern Europe might be more complex than the traditional view (Brauna-Morževska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%